New Mexico : wild and beautiful - Parent, Laurence; Drabanski, Emily (Helena, Mont. : Farcountry Press, 2007)
This is a dynamic showcase of work by photographer and New Mexico native Laurence Parent. With informative captions by Emily Drabanski, this collection of photographs serves as a timeless triburte to the state affectionately called the Land of Enchantment.
Keywords: New Mexico - Photographs; Pictorial works